Effects of Honey Addition on Antioxidative Properties of Different Herbal Teas - Toydemir Gamze; Capanoglu Esra; Kamiloglu Senem; Firatligil-Durmus Ebru; Sunay Asli E.; Samanci Taylan; Boyacioglu Dilek (Polish Journal of Food and Nutrition Sciences)
Tea and herbal infusions are among the major contributors of phenolic compounds, specifically flavonoids, in our daily diet. Honey is another antioxidant-rich food that is widely used as a natural sweetener. In this work, the effects of honey addition on antioxidant properties of different herbal teas were investigated. For this purpose, 2 different types of honey (flower and pine honey) were added into 9 different herbal teas (melissa, green tea, rosehip, sage, echinacea, fennel, linden, daisy, and ginger) at 4 different temperatures (55°C, 65°C, 75°C, and 85°C), and the changes in the content of total pheolics, total flavonoids, and total antioxidant capacity were determined. The total phenolic content and the total antioxidant capacity of the honey-added-tea samples were found to be increased (up to 57% for both), especially with pine honey and at higher temperatures of honey addition. The findings of this study supported the use of honey as a natural sweetener in tea in order to be able to benefit from the health-enhancing antioxidative properties of these two promising food products.